Impact of the University Library Usage for Academic Purpose by Undergraduates in Sri Lankan Universities on their Academic Performance - Karannagoda, Neluka Maduranga (University of Colombo, 2019)
The library is a result of social evolution and the present library is not something born overnight. The contribution made by the library in transferring the knowledge possessed by one generation to another is immense. World history has established the fact that the center of knowledge of a university is the library. Government University libraries in Sri Lanka are maintained in a complex and large space incurring a great expense with the assistance of a big cadre. Though the situation is this, it seems that the undergraduates do not effectively use the university library for their education and they tend to extract informal information from various unauthenticated sources. As these libraries are maintained by public funds library authorities are responsible to demonstrate their value, contribution and effectiveness for the academic success of the undergraduates. However, up to now, Sri Lankan Government University libraries have not developed an appropriate and practical procedure for this purpose. As such, it is a timely requirement to have a research study in this regard to measure the contribution made by the university library to the university to produce graduates, the main output of any university. Further, if it is possible to demonstrate a positive relationship between the university undergraduates’ library usage for academic activities and their results, it can be conveyed to the undergraduates through the academic staff. By this means the students’ tendency to use the university library can be enhanced. In addition, it is necessary to explore this relationship in relation to faculties and respective years. If students of any faculty do not show a proper relationship, necessary action may be taken to find the reasons for such a performance and to avoid shortcomings. Understanding the nature of the relationship will help to regulate the distribution of library resources. As such, in this research, it is intended to analyze the relationship between the undergraduates’ university library usage for academic purpose and their academic performance as a whole and with regards to the gender, faculties and different library usage types. Also, it is expected to explore the different sources used by undergraduates to gather information for academic purpose other than the university libraries. Further, it is expected to find out whether there is any significant difference between the academic performance of the undergraduate users and non-users of the university library for academic purposes. Finally, it is intended to introduce a systematic way to maintain the libraries to demonstrate the benefits they offer to the society by taking a sample of 1293 undergraduates using the stratified and random sampling techniques and by administering a simple questionnaire. A pilot study was conducted using 20 undergraduates selected randomly (nearly 15% of the sample size of the undergraduates of the Faculty of Management and Finance, University of Colombo). Data were analyzed using SPSS statistical software. According to the pilot study, only one library usage type (Usage of Photocopy service, Scanning and Other services) shows a positive significant relationship with the academic performance of the undergraduates. However, the other library usage types did not show a significant relationship with the undergraduates’ academic performance. Therefore it is recommended to conduct the whole study and come to a conclusion.
Keywords: academic performence; library usage; undergraduate studies